2017
DOI: 10.5271/sjweh.3644
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of levels and patterns of occupational exposure to 1,3-butadiene

Abstract: Objectives 1,3-butadiene is classified as carcinogenic to human by inhalation and the association with leukemia has been observed in several epidemiological studies. The aim of this study was to evaluate data about occupational exposure levels to 1,3-butadiene in the Italian working force. Methods Airborne concentrations of 1,3-butadiene were extracted from the Italian database on occupational exposure to carcinogens in the period 1996-2015. Descriptive statistics were calculated for exposure-related variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Co-exposures to benzene, 1,3-butadiene and PAHs (cluster n° 4) are well known among oil refinery workers, even if exposure levels are currently low [ 20 , 21 ]. However, a similar pattern of exposure can also occur in the service sector, with a share in women too as reported in a previous study [ 17 ]. In the present study, this co-exposure pattern among women (cluster n° 4) was found mainly in the sector of gambling and betting activities, for exposures coming from secondhand smoke.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Co-exposures to benzene, 1,3-butadiene and PAHs (cluster n° 4) are well known among oil refinery workers, even if exposure levels are currently low [ 20 , 21 ]. However, a similar pattern of exposure can also occur in the service sector, with a share in women too as reported in a previous study [ 17 ]. In the present study, this co-exposure pattern among women (cluster n° 4) was found mainly in the sector of gambling and betting activities, for exposures coming from secondhand smoke.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, exposure levels to hardwood dust were higher in male workers, while women had higher levels of exposure to formaldehyde, a chemical recently added in the carcinogens list of EU. A study based on SIREP data has shown higher mean exposure levels to formaldehyde in sectors with a higher proportion of women exposed such as wood industry and healthcare [ 17 ]. The concurrent occupational exposure to hardwood dust and formaldehyde emerges as a critical issue, involving, according to our data, a relevant number of women too, mainly in small-size enterprises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between occupational exposure to 1,3-butadiene and the occurrence of cancers of hematolymphatic organs, mainly leukemia, was observed in large occupational cohort studies (Orozco et al, 2019; Sadeghi-Yarandi et al, 2020). The International Agency for Research on Cancer (IARC) has identified this chemical agent as carcinogenic to human by inhalation (Scarselli et al, 2017). In addition, previous studies have shown that some metabolites of 1,3-butadiene (like monoepoxide, diepoxide, and epoxydiol) are suspected of causing genetic defects.…”
Section: Introductionmentioning
confidence: 99%
“…1,2:3,4‐Diepoxybutane (DEB) is the most potent active metabolite of the environmental chemical 1,3 butadiene (BD) [1] . BD is a regulated hazardous air pollutant that is genotoxic, mutagenic, and carcinogenic [1–4] . Human exposure to BD occurs through inhalation of the compound found at industrial sites, in automobile exhaust, cigarette smoke, and forest fires.…”
Section: Introductionmentioning
confidence: 99%